2016
DOI: 10.1111/gcb.13563
|View full text |Cite
|
Sign up to set email alerts
|

Warming of subarctic tundra increases emissions of all three important greenhouse gases – carbon dioxide, methane, and nitrous oxide

Abstract: Rapidly rising temperatures in the Arctic might cause a greater release of greenhouse gases (GHGs) to the atmosphere. To study the effect of warming on GHG dynamics, we deployed open-top chambers in a subarctic tundra site in Northeast European Russia. We determined carbon dioxide (CO ), methane (CH ), and nitrous oxide (N O) fluxes as well as the concentration of those gases, inorganic nitrogen (N) and dissolved organic carbon (DOC) along the soil profile. Studied tundra surfaces ranged from mineral to organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
160
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(197 citation statements)
references
References 82 publications
13
160
3
Order By: Relevance
“…Field studies show that the presence of vegetation reduces N 2 O emissions (16)(17)(18), also observed here, by lowering the mineral N supply in the rooting zone of vascular plants (Fig. 3 B and C).…”
Section: Role Of Soil Moisture and Vegetation In Regulating Arctic N 2 Osupporting
confidence: 77%
See 2 more Smart Citations
“…Field studies show that the presence of vegetation reduces N 2 O emissions (16)(17)(18), also observed here, by lowering the mineral N supply in the rooting zone of vascular plants (Fig. 3 B and C).…”
Section: Role Of Soil Moisture and Vegetation In Regulating Arctic N 2 Osupporting
confidence: 77%
“…In previous studies, we identified patches of bare peat in permafrost peatlands as hot spots for N 2 O emissions in subarctic tundra (16,17). Furthermore, an increase in growing season temperature without causing permafrost thaw not only increases N 2 O emissions from these hot spots, but also triggers N 2 O emissions from vegetated tundra peatlands (18), which cover large areas of the Arctic. This highlights the important role that peatlands may play in promoting Arctic N 2 O emissions in the future.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…We used ranked correlated surfaces to visualize the synthetic maps for visualization purposes (Schrenk et al, ). The chemical and physical properties including organic matter content, respiration rate, C:N ratios, and bulk density were extracted from literature data on field measurements (Gil et al, ; Repo et al, ; Voigt et al, ) and mapped as shown in Table S1 (and Figure S5 for respiration rates from different ecosystems). The upscaled biophysical model is linked to hydrologic and thermal modules to estimate soil water content and temperature profiles (see supporting information Figure S2 and Ebrahimi & Or, ).…”
Section: Large‐scale Temporal and Spatial Variations In Soil Ghg Emismentioning
confidence: 99%
“…Overall, these results demonstrate that soil moisture regulates the responses of N 2 O emissions to experimental warming, highlighting the necessity to consider the warming-induced drying effect when estimating the magnitude of N 2 O emissions under future climate warming. Key words climate warming; nitrous oxide; ammonia-oxidizing archaea; ammonia-oxidizing bacteria; QinghaiXizang Plateau Wang GQ, Li F, Peng YF, Chen YL, Han TF, Yang GB, Liu L, Zhou GY, Yang YH (2018 (Mosier, 2008;Shi et al, 2012;Voigt et al, 2016), 然而, 也有少数研究发 现增温会抑制土壤N 2 O的排放 或者 未造成显著影响 (Ward et al, 2013;徐冰鑫等, 2014), 计算: Chapin III et al, 2011) …”
mentioning
confidence: 99%